SISTEM PEMERINTAHAN PRESIDENSIAL DALAM NEGARA KESATUAN REPUBLIK INDONESIA - Arnita Jamil (Puslatbang KHAN, 2020)
The Indonesian reforms in 1999 causes a lot of changes including the system and practice of the state administration, among others the purification of the presidential system of government. This research uses the method of juridical- normative law reseach. The authors collects secondary data relating to the issues discussed and then analyzed. The results show that after the amendments to the 1945 Constitution, the presidential government system are stronger than before. This can be seen, among others, from the strong position of the President where the President and /or Vice President is directly elected by the people, the President is no longer responsible to the representative body (MPR), the president is a single executive where the vice president and ministers are assistant to the president who is responsible to the president, the President holds office for five years (fixed). The President and / or Vice President can no longer be dropped for reasons of political or government policies but can only be imposed due to violations of the law (impeachment).